King on screen [videorecording (DVD)] - Pike, Nicholas (Dark Star, 2023)
The Shining, Carrie, It, Misery, Stand By Me; more than 60 of Stephen King's novels have been adapted into films. King on Screen pulls back the curtain and offers an intimate sit down with the filmmakers who brought King's stories to life.